Scoping Review and Bibliometric Analysis of the Term “Planetary Health” in the Peer-Reviewed Literature - Rossa-Roccor, Verena; Acheson, Emily Sohanna; Andrade-Rivas, Federico; Coombe, Michelle; Ogura, Saori; Super, Laura; Hong, Andy (Frontiers in Public Health, 2020)
Background: Planetary health is an emerging holistic health field to foster interdisciplinary collaborations, integrate Indigenous knowledge, facilitate education, and drive public and policy engagement. To understand to what extent the field has successfully met these goals, we conducted a scoping review and bibliometric analysis. Methods: We searched 15 databases from 2005 to 2019 for peer-reviewed publications with the term “planetary health” in the title, abstract and/or keywords, with no language or geographical location limitations. We classified results into four categories (commentaries, comprehensive syntheses, educational material, and original research) and categorized original research according to expert-derived planetary health themes. Our bibliometric analysis highlighted publications over time, collaborations, and networks of keywords. Findings: Only 8.1% (n = 22) were research articles. Publications rose rapidly from 8 to 64 publications per year in 2015–2018. The top five author affiliation countries for most publications were the US, UK, Australia, Canada, and New Zealand, and the top five collaborations were a subset of pairwise combinations between the US, UK, Australia, and Canada. The most common author keywords were the following: planetary health, climate change, ecology, and non-communicable diseases. Keyword co-occurrences clustered around high-level concepts (e.g., Anthropocene) and food system-related topics; two clusters lacked a theme. Interpretation: We show that the term planetary health is used mainly in commentary-like publications, not original research. Additionally, more global collaborations are lacking. Interdisciplinary work, as represented by keyword co-occurrence networks, is developing but could potentially be extended. The planetary health community should promote more worldwide research and interdisciplinary collaborations.